2022
DOI: 10.1136/bmjpo-2021-001397
|View full text |Cite
|
Sign up to set email alerts
|

Disability in children: a global problem needing a well-coordinated global action

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, conduct, reporting or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Collaborative models involving parental inputs, training of special education teachers and providing inclusive education that also co-locates therapists operating in the same setting would bring African countries closer to achieving effective education for CALWD ( 38 ). To achieve these wide-ranging measures, interventions including policy development and implementation as and changes in social-cultural attitudes toward education for CALDW would be required ( 9 , 10 , 27 ).…”
Section: School Readiness and Optimizing Education For Calwd In Africamentioning
confidence: 99%
See 3 more Smart Citations
“…Collaborative models involving parental inputs, training of special education teachers and providing inclusive education that also co-locates therapists operating in the same setting would bring African countries closer to achieving effective education for CALWD ( 38 ). To achieve these wide-ranging measures, interventions including policy development and implementation as and changes in social-cultural attitudes toward education for CALDW would be required ( 9 , 10 , 27 ).…”
Section: School Readiness and Optimizing Education For Calwd In Africamentioning
confidence: 99%
“…To achieve these wide-ranging measures, interventions including policy development and implementation as and changes in social-cultural attitudes toward education for CALDW would be required ( 9 , 10 , 27 ). African countries would need to commit advancements to improve the understanding of the general public regarding education for CALWD in order to realize the vision of an inclusive education ( 17 , 27 , 38 ).…”
Section: School Readiness and Optimizing Education For Calwd In Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Olusanya et al ( 10 , 11 ) reported that 95% of all children with developmental disabilities including ASD live in low-or middle-income countries (LMIC) ( 10 , 11 ), yet there is little information on how these children are identified, evaluated, treated and educated ( 12 15 ). In a scoping review of all autism research in sub-Saharan Africa, Franz and colleagues identified that less than 1% of the world's autism research had taken place in Africa, and that no studies had examined health or education systems for children with autism ( 15 ).…”
Section: Introductionmentioning
confidence: 99%